Effect of various W-beam guardrail post spacings and rail heights on safety performance. (9th November 2015) - Teng, Tso-Liang; Liang, Cho-Chung; Tran, Thanh-Tung
W-beam guardrails are the most widely used road safety barriers worldwide. They are used for protecting vehicle occupants on dangerous areas of roadways. All road safety barriers used on European highways are designed according to the European standard EN 1317. Conventionally, such road safety barriers have the following dimensions: a 750-mm height from the top of the W-beam to the ground and a 1.33-, 2-, or 4-m post spacing. This study applied the finite element code LS-DYNA for evaluating the safety performance of an AG04-2.0 A-type barrier, which was designed using three post spacings and various rail heights, when impacted by a 900-kg small passenger car. Eight crash test simulations were conducted for evaluating the crashworthiness of the AG04-2.0 barrier according to the European Standard EN 1317. A baseline model was developed and validated against the existing crash test models. The results showed that the various post spacings (1.33, 2, and 4 m) and rail heights (600, 650, 700, 750 and 800 mm) enabled the AG04-2.0 barrier to withstand the impact of the 900-kg car, satisfying the EN 1317 criteria (i.e. TB11 test). The 2000-mm post spacing and 700-mm rail height were considered the optimal dimensions for AG04-2.0 road safety barriers.